PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL SNOWBALL THROWING BERBANTUAN MEDIA POWTOON DI KELAS IV SDN 01 BANDAR BUAT - Genisa, Tiara; Wahyuni, Etri; Bungsu Ladiva, Hasmai; Meizatri, Ranti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of fourth-grade students at SDN 01 Bandar Buat, caused by the lack of active student involvement, suboptimal selection of learning models, and limited use of technology-based learning media in Pancasila Education. This research aims to improve student learning outcomes in Pancasila Education using the Snowball Throwing model assisted by Powtoon media in the fourth grade of SDN 01 Bandar Buat. This study employed Classroom Action Research (CAR) using qualitative and quantitative approaches, conducted in two cycles consisting of planning, implementation, observation, and reflection. The research instruments consisted of test sheets and non-test sheets. Data collection used test and non-test techniques. The research subjects were the classroom teacher and fourth-grade students of SDN 01 Bandar Buat. The results showed that: First, the average RPPM in cycle I was 93.75% (SB), increasing in cycle II to 100% (SB). Second, teacher activity in cycle I averaged 86.10% (B), increasing in cycle II to 96.34% (SB). Third, student activity in cycle I averaged 83.33% (B), increasing in cycle II to 94.44% (SB). Fourth, student learning outcomes in cycle I averaged 74.90 (C), increasing in cycle II to 88.49 (SB). It can be concluded that the Snowball Throwing model assisted by Powtoon media can improve student learning outcomes in Pancasila Education in the fourth grade of SDN 01 Bandar Buat.